The Influence of Puncture Valve Wear on Bosch Pump Pressure and Main Engine Performance: A Quantitative Analysis of KM. Tanto Bersinar - Setiawan, Langgeng; Prawoto, Agus; Ratnaningsih, Dyah; Robbi, Shofa Dai; Kristiyono, Antonius Edy (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The Main Mover Diesel Engine or Main Engine on a ship is the main device responsible for moving the ship forward and backward. The diesel engine fuel system, which includes the Bosch Pump, is a critical component in maintaining the engine's performance by providing the fuel necessary for combustion and propulsion of the vessel. The injector, which is used to spray fuel into the engine cylinder, is an important part of the system that supports the efficient combustion process in the main engine. The method used is a quantitative method which includes the collection and analysis of numerical data. By conducting surveys, experiments, or secondary data analysis, researchers can find patterns or generalizations in a larger population. By using quantitative methods, it will be possible to determine the cause of the decrease in Bosch pump pressure on the ship MV.Tanto Bersinar. The analysis of running hoaurs of puncture valve on the fuel injection pump for cylinder 1-8 demonstrates that the wear of puncture valve especially in cylinder 2 with 4.970 hours approaching the planned maintenance system (PMS )limit of 5.000 hours significantly affects injection pressure stability ,combustion,quality ,and main engine officiency ,which can be restored throngh critical component replacement,inspections close to PMS and injection pump recalibration.